Oxidative stress and disease: atherosclerosis - Poli, Giuseppe (Henry Stewart Talks, 2019)
Oxidative stress, inflammation and fibrosis, Redox-dependent expression of pro-fibrogenic cytokines, Formation and evolution of fibrotic plaque: the primary role of inflammation, LDL lipid oxidation products, Lipid oxidation during the genesis of atherosclerotic lesion, Enzymatic and non-enzymatic lipid oxidation products, Pro-inflammatory and pro-fibrogenic effects of 4-hydroxy-2-alkenals, Oxysterols of pathophysiological interest, Oxysterols and atheroma formation, Pro-inflammatory effects of cholesterol oxidation products